Natriuretic peptide-guided treatment for heart failure: a systematic review and meta-analysis - McLellan, J; Bankhead, C; Oke, J; Hobbs, R; Taylor, C; Perera-Salazar, R (BMJ, 2019)
Background: GUIDE-IT, the largest trial to date, published in August 2017, evaluating the effectiveness of natriuretic peptide-guided treatment of heart failure, was stopped early for futility on a composite outcome. However, the reported effect sizes on individual outcomes of all-cause mortality and heart failure admissions are potentially clinically relevant. Objective: This systematic review and meta-analysis aims to combine all available trial level evidence to determine if natriuretic peptide-guided treatment of heart failure reduces all-cause mortality and heart failure admissions in patients with heart failure. Study selection: Eight databases, no language restrictions, to November 2017 were searched for all randomised controlled trials comparing natriuretic peptide-guided treatment versus clinical assessment alone in adult patients with heart failure. No language restrictions were applied. Publications were independently double screened and extracted. Fixed-effect meta-analyses were conducted. Findings: 89 papers were included, reporting 19 trials (4554 participants), average ages 62-80 years. Pooled risk ratio estimates for all-cause mortality (16 trials, 4063 participants), were 0.87, 95% confidence interval 0.77 to 0.99, and 0.80, 95% CI 0.72 to 0.89, for heart failure admissions (11 trials, 2822 participants). Sensitivity analyses, restricted to low risk of bias, produced similar estimates, but were no longer statistically significant. Conclusions: Considering all the evidence to date, the pooled effects suggest that NP-guided treatment is beneficial in reducing heart failure admissions and all-cause mortality. However, there is still insufficient high quality evidence to make definitive recommendations on the use of natriuretic peptide-guided treatment in clinical practice.